Malrotation of the intestine and preduodenal portal vein associated with abdominal situs inversus: A case report - Díaz, Rosa; Lugo-Vicente, Humberto (Puerto Rico Health Sciences Journal, 2007)
Abdominal situs inversus is a rare condition usually associated with malformations of asymmetric organs such as the heart, liver, spleen and malrotation of the intestines. A case of abdominal situs inversus with intestinal malrotation and preduodenal portal vein is reported. Patient underwent prophylactic Ladd’s procedure and preduodenal portal vein was left undisturbed during surgery. This case highlights the importance of rigorous investigation of anatomic features prior to surgery in a patient with heterotaxia. The authors advocate radiological investigation of patients with heterotaxia and prophylactic Ladd’s procedure in those with intestinal malrotation.